Tingkat Kepuasan Pasien BPJS Terhadap Pelayanan di Depo Farmasi Rawat Jalan RSUD Kota Bogor Tahun 2024: BPJS Patient Satisfaction Levels with Services at the Outpatient Pharmacy Depot of Bogor City Regional General Hospital in 2024 - Rangga Adliano Pratama; Leli Nurlaeli; Nina Nina (UIMA Press, 2025)
Patient satisfaction with pharmaceutical services is a feeling of pleasure after receiving services that meet their expectations. Satisfaction surveys are used as indicators of service quality assessment. This study aims to determine the level of satisfaction of BPJS outpatient patients with pharmaceutical services at the Outpatient Pharmacy Installation of the Bogor City Regional General Hospital in 2024. The study was an observational prospective study with a population of 11,393 patients and a sample of 99 respondents using the Slovin formula and accidental sampling technique. The research instrument was a questionnaire, with data analysis using a Cartesian diagram. The results showed that of the 99 respondents, 89 patients (89.9%) were satisfied and 10 patients (10.1%) were dissatisfied with the pharmaceutical services. Based on the dimensions of tangibles (direct evidence), responsiveness, and assurance, all patients (100%) expressed satisfaction. In terms of reliability and empathy, most patients were also satisfied. Overall, the pharmacy services at the Bogor City Hospital were rated as very good by BPJS outpatients. Recommendations for the outpatient pharmacy at the Bogor City Hospital include providing certainty regarding the time for picking up medication.